1H magnetic resonance spectroscopy reveals neuronal injury in a simian immunodeficiency virus macaque model. - Tracey, I; Lane, J; Chang, I; Navia, B; Lackner, A; González, R (1997)
Infection with human immunodeficiency virus (HIV) commonly results in neurologic disease called the AIDS dementia complex. Neuronal loss and injury have been found in the HIV brain, but the underlying mechanisms are not understood. The simian immunodeficiency virus (SIV)-infected macaque is an excellent animal model for HIV infection, but neuronal loss has not been demonstrated. To determine whether neuronal damage occurs in the SIV brain, we quantified the neuronal marker N-acetylaspartate (NAA) using proton magnetic resonance spectroscopy (1H-MRS) in brain extracts of control and SIV-infected macaques and correlated these findings with histologic analyses. We found reduced NAA in the SIV-infected animals compared with controls (2.94 +/- 1.37 versus 6.21 +/- 1.73 micromol/g of wet weight; p = 0.004). A significant decrease in NAA was also found in SIV-infected animals sacrificed in the acute stages of infection 9 or 10 days after inoculation with SIVmacYnef. We conclude that SIV infection of rhesus macaques results in neuronal damage that is demonstrable shortly after infection and that 1H-MRS may be used to measure such injury. The results further support the SIV macaque as a useful model to study the mechanisms of neuropathogenesis by HIV.